Ռոսլինի՝ Մալաթիայի Ավետարանի մի էջի ընդօրինակություն - Մանուկյան, Սեդա
The article discusses the Missal copied in Keozlev (modern Yevpatoria/ Eupatoria in Crimea) in 1747 (MS. M7658). An image of the Raising of Lazarus is glued to the cover of the manuscript. As we have found out, it is an excellent copy of a miniature from T‘oros Ṙoslin’s Gospel of Malat‘ia. Our study of this fragment opens a new page in the history of the Malat‘ia Gospel. It seems possible that this famous manuscript was at one time kept in a Crimean scriptorium, where the fragment was copied. Thus, before reaching Malat‘ ia the manuscript may have appeared in Crimea, probably in the 14th century. В статье рассматривается Служебник (ММ 7658), написанный в 1747 г. в Кеозлеве (Крым, ныне Евпатория). К переплету подклеена миниатюра с изображением Воскрешения Лазаря, которая, как нам удалось выяснить, является великолепной копией с миниатюры Рослина из Малатийского Евангелия (ММ10675). Изучение этого фрагмента позволяет предположить, что данное Евангелие какое-то время, прежде чем попасть в Малатию, с XIV века хранилась в одной из школ Крыма, где и была скопирована. Стилистические и иконографические особенности также позволяют датировать фрагмент XIV веком.
Keywords: Մանրանկարչություն; Ավետարան